Regional Legal Assistance - Abdul Fatah (Universitas Muhammadiyah Sidoarjo, 2015)
Legal aid policy in the area carried out on several considerations including: Implementation of the authority given to the legal aid act, granting the guarantee and protection of access to justice and equality before the law in the area, equitable distribution of justice and increase public awareness and understanding of the law, and legal implications that accompanied the emergence of the right to legal counsel without pay and the right to choose the legal settlement. How To Cite Fatah, A. (2015). Regional Legal Assistance. Rechtsidee, 2(1), 1-10. doi:http://dx.doi.org/10.21070/jihr.v2i1.7